EFFORTS TO OVERCOME LOAD UNBALANCE ON LOW VOLTAGE NETWORKS USING PHB – SR EQUIPMENT (CONNECTION EQUIPMENT FOR HOME CONNECTIONS) AT PT. PLN PERSERO ULP BINJAI TIMUR - Dicky Prasetya; Hamdani; Siti Anisah (Sean Institute, 2022)
Load imbalance in an electric power distribution system often occurs in the field. This is a single-phase load on different Low Voltage Network subscribers due to the large number of additional electrical loads that do not pay attention to system load imbalances. As a result of this imbalance, a current appears in the neutral of the transformer. The current flowing in the neutral of this transformer causes losses (technical losses/losses), namely losses due to the neutral current in the neutral conductor of the transformer and losses due to neutral current flowing to the ground. By realizing PHB SR (Connecting Equipment for House Connections) it is able to balance the load on the Low Voltage Network on a regular and continuous basis so as to reduce technical losses (losses), simplify the Splicing Field in technical connection of House Connections (SR) on the Pole, improve aesthetics and neatness Network System.